Ribonucleic Acid Synthesis in Cells Infected with Influenza Virus - Nayak, D. P. (1968)
Virus-specific ribonucleic acid (RNA), synthesized in influenza virus-infected cells from 3.5 to 7.5 hr after infection, was studied. After velocity centrifugation in sucrose, three peaks of virus-specific RNA could be identified: 34S, 18S, and 11S. These RNA species are predominantly single-stranded and consist of 90% viral (plus) and 10% complementary (minus) RNA strands. Most (75%) of the complementary RNA is single-stranded, i.e., not part of RNA duplexes or replicative intermediates. The 34S RNA species is an aggregate of 18S and 14S RNA species. Both 18S and 11S RNA species are relatively heterogenous compared to 18S ribosomal RNA, and these species probably contain different RNA molecules having closely related sedimentation coefficients.